Acute Pancreatitis as the Initial Presentation of Systematic Lupus Erythematosus - Jia, Yi (Hindawi Publishing Corporation, 2014)
Systematic lupus erythematosus (SLE) is a multisystem disease, including the gastrointestinal system in about half of SLE patients. As a rare complication of SLE, acute pancreatitis presents as generalized flare-ups in most cases of patients previously diagnosed with SLE. Here we report a rare case of acute pancreatitis as the initial presentation with later diagnosis of SLE.